Analysis Of Motivation For Learning Sciences Based On Gender Of Primary School Students - La Lulu Ode Bora; Sutrisno, Sutrisno (Council: Education Journal of Social Studies, 2025)
The aim of this research is to determine the description of social studies learning and the differences in learning motivation of Class V students at SDN 09 Katobu. The research method used is qualitative research. Research Results Show that; Description of the motivation for studying social studies for class V students at SDN 09 Katobu, where students consider social studies as a difficult or boring subject, this can reduce motivation to learn. Female students show higher intrinsic motivation in studying social studies. Meanwhile, male students have low motivation, because they focus more on playing and their social studies learning outcomes are relatively low